FC030: Diagnostic Yield of Exome Sequencing in Hypertensive Nephropathy. (3rd May 2022) - Serre, Justine; Rafat, Cédric; Raymond, Laure; Dancer, Marine; Werion, Alexis; Nobile, Giulio; Bobot, Mickaël; Rondeau, Eric; Mesnard, Laurent; Doreille, Alice
Abstract: BACKGROUND AND AIMS: Hypertensive nephrosclerosis ranks as one of the most frequent causes of chronic kidney disease (CKD) worldwide and is deemed to be especially prevalent among patients of African ancestry [1 ]. The very existence of hypertensive nephropathy has been called into question, especially in young adults. Its diagnostic framework is based on non-specific clinical criteria, and its histopathological features are in fact unspecific. Genetic testing with exome sequencing (ES) has emerged as a comprehensive tool to detect Mendelian diseases in nephrology with a significant number of post-hoc re-established diagnoses [2 ]. Nevertheless, ES has yet to be incorporated into the diagnostic workup of patients with hypertensive nephropathy consistently. This study aimed to investigate the diagnostic yield of ES in patients with a clinical diagnosis of hypertensive nephropathy. METHOD: Since September 2018, ES is readily available as part of the routine diagnostic workup in our institution. The indication of ES includes hypertensive nephropathy of early onset (i.e. <45 years old). We retrospectively collected the ES performed in the context of hypertensive nephropathy [3 ] in our institution between September 2018 and February 2021. RESULTS: A total of 128 patients were sequenced in the context of hypertensive nephropathy with early-onset. Women were 29 (22.7%), the mean age was 43 (35; 51) years and 60% of them were patients of African ancestry. The main indications of ES was an early onset of CKD (47%), a family history of kidney disease (8%) or both (18%). We detected diagnostic variants (ACM class 4/5) in 22 of the 128 patients (17.2%) encompassing a total of 16 different monogenic disorders. Two diseases accounted for more than half of the genetic diagnoses: nephronophthisis ( n  = 7, 32%) and Alport syndrome ( n  = 5, 23%). Complement variation did not account for a significant part of the diagnosis. The diagnostic yield of ES was lower in patients of African ancestry (diagnostic yield of 10.4% versus 27.4% in the non-African ancestry patients; P = 0.01). Co-segregation data was lacking in patients of African ancestry, with significantly more ES performed in singleton (96% compared with 76% in non-African ancestry patients; P < 0.001). In addition to disease reclassification, genetic diagnosis enabled guidance for family counseling ( n  = 11, 50% of positive patients) and thus helped for potential related donor selection for transplantation. In the whole cohort, ES results modified the therapeutic in 6 patients (5%) and ruled out potential recurrence in the graft in 10 patients (8%). CONCLUSION: Physicians should be wary of tentative diagnosis of nephrosclerosis, especially in patients of non-African ethnic background. Instead, it should prompt genetic investigations, which overturned the initial diagnosis in 17% of the cases. The lower diagnostic yield of ES in patients of African ancestry in our cohort might partly be due to the lack of available co-segregation data, as well as the underrepresentation of subjects of African ancestry in the reference genome.